Reconstruction of intercalary bone defect after resection of malignant bone tumor - Karem M Zekry; Norio Yamamoto; Katsuhiro Hayashi; Akihiko Takeuchi; Ali Zein AA Alkhooly; Ahmed Saleh Abd-Elfattah; Ahmed Nady Saleh Elsaid; Adel Refaat Ahmed; Hiroyuki Tsuchiya (Journal of Orthopaedic Surgery, 2019)
Due to accurate preoperative imaging techniques, early diagnosis and effective chemotherapy, many tumors arising in the metaphyseo-diaphyseal regions of long bones can be segmentally resected with joint preservation. The intercalary resection of malignant bone tumor results in a bone defect which can represent a challenging reconstructive problem. The most commonly used surgical reconstructive options for these defects include biologic reconstructions such as allografts, vascularized fibular grafts, autogenous extracorporeally devitalized tumor bearing bone graft, combination of allografts or devitalized autografts with vascularized fibular grafts, segmental bone transport, or induced membrane technique. Nonbiologic reconstructions, on the other hand, use intercalary endoprostheses. Every patient should be carefully evaluated and the reconstructive option should be individually selected. The aim of this article is to discuss the surgical options of reconstruction of bone defects after intercalary resection of malignant bone tumors with reviewing of their indications, advantages, disadvantages and complications.